Resilience: an entry point for African health promoting schools?. Issue 3 (2014) - ,
Abstract : Purpose – The purpose of this paper is to provide a review of an Australian health promoting schools (HPS) project to identify key features of the concept of resilience and how it can be used in a school setting to develop and strengthen protective factors in young people, as a mechanism for improving social functioning and reducing involvement in risk behaviours.Design/methodology/approach – Methods used in the "Resilient Children and Communities" project are described. Then a revue of the academic literature published on theoretical and empirical findings from the "Resilient Children and Communities" project is presented.Findings – The papers reviewed indicate there is a developing body of evidence to show that the "HPS" is an efficient and effective approach to building resilience amongst school children. Underpinned by Bronfenbrenner's broad ecological framework, benefits have been derived not only for students, but for the whole school community. Such benefits include not only building self‐esteem and self‐efficacy, peer relationships and relationships between students, teachers and parents, but also school connectedness and feelings of belonging.Practical implications – The findings from this project provide a strong evidence base identifying the central role of "resilience" in the school culture. This role is cross‐cultural and transnational and evidence that resilience can strengthen protective factors has clear implications for the African context, where communicable diseases and neglected tropical diseases pose intractable problems, typically in resource restricted environments.Originality/value – These findings provide insight into the central role of the school setting in building resilience. Resilience, in turn, can help students survive and thrive under challenging and adverse conditions. Acknowledgements : The author gratefully acknowledges funding support for the Resilient Children and Communities project from Queensland Health. He also wishes to acknowledge and thank the research team of Dr Carla Patterson, Dr Jing Sun, Dr Kate Lemerle and Michael Hardie. The funder played no role in either the study design or the submission.